Valtrex therapy for Epstein-Barr virus reactivation and upper respiratory symptoms in elite runners - Cox, A. J.; Gleeson, M.; Pyne, D. B.; Saunders, P. U.; Clancy, R. L.; Fricker, P. A. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The aim of the study was to examine the effectiveness of prophylactic administration of the antiviral agent Valtrex for control of Epstein-Barr virus (EBV) reactivation and upper respiratory symptoms in elite distance runners. METHODS: Twenty elite male distance runners were randomized into a 4-month double-blind, placebo-controlled cross-over trial. Saliva samples were collected weekly and mucosal immune status assessed by measurement of secretory IgA (SIgA) using an enzyme-linked immunosorbent assay (ELISA). EBV reactivation was monitored at the same time by detection of EBV in saliva using a quantitative real-time polymerase chain reaction. The initial EBV status of the runners was determined by detecting EBV antibodies in serum using an ELISA. Upper respiratory symptoms were recorded using self-reporting illness logs. RESULTS: There was no evidence of any marked change in maximal oxygen uptake (P = 0.86), training volume (P = 0.30), or mucosal immunity (P = 0.21) over the study period. Valtrex treatment resulted in an 82% reduction in the detectable EBV load in saliva for EBV seropositive runners compared with the placebo treatment (P = 0.04). The incidence of upper respiratory symptoms was not reduced by Valtrex treatment. CONCLUSIONS: The prophylactic administration of Valtrex reduced EBV reactivation but was not an effective intervention strategy for limiting upper respiratory symptoms in this cohort of elite distance runners. The upper respiratory symptoms in the distance runners could not be directly attributed to infection and may be of a noninfectious inflammatory nature.